Предмет: Алгебра,
автор: qlert
помогите плиииз!!!!!!
Приложения:
Ответы
Автор ответа:
0
(12a-3b) / (12a+3b) = 3(4a-b) / 3(4a+b) = (4a-b) / (4a+b) =
(4*(-³/₄)-(-⁵/₆)) / (4*(-³/₄)+(-⁵/₆)) = (-3+⁵/₆) / (-3-⁵/₆) = (-2⁶/₆+⁵/₆) / (-3⁵/₆) =
(-2¹/₆) / (-3⁵/₆) = -2¹/₆ : (-3⁵/₆) = -¹³/₆ : (-²³/₆) = -¹³/₆ * (-⁶/₂₃) = ¹³/₂₃.
(4*(-³/₄)-(-⁵/₆)) / (4*(-³/₄)+(-⁵/₆)) = (-3+⁵/₆) / (-3-⁵/₆) = (-2⁶/₆+⁵/₆) / (-3⁵/₆) =
(-2¹/₆) / (-3⁵/₆) = -2¹/₆ : (-3⁵/₆) = -¹³/₆ : (-²³/₆) = -¹³/₆ * (-⁶/₂₃) = ¹³/₂₃.
Похожие вопросы
Предмет: Биология,
автор: tamarasuvorova373
Предмет: Русский язык,
автор: robopidorovich
Предмет: Английский язык,
автор: kirillzerox
Предмет: Математика,
автор: Asyatsechoeva
Предмет: Биология,
автор: parnazz